Georges Paulin (1902-1942): A Legendary Dentist, a Resistance Hero - Xavier Riaud (Journal of Dental Problems and Solutions - Peertechz Publications, 2017)
A modest childhood...brilliant studies Georges Paulin was born in Paris in 1902 [1]. From a humble background, he was a gifted child who soon got bored in school. Very early, he showed outstanding drawing skills. In 1918, his mother was killed during the bombings of the capital. He would never fully get over it. At the age of 14, he became a dental technician and was soon recognized for his talents. He opened his own business and went back to school to become a dental surgeon. Following in his brother's footsteps, he graduated from Garancière. This professional activity only helped him to finance his passion. A beneficial rain "It was in 1927 that his research began. He was leaning against the window of his dental prosthesis laboratory in Nice when a violent and stormy shower fell on the city. On the opposite pavement stood a magnificent Delage convertible and in spite of all his efforts, its owner could not close the hood before the leather and velvet interior had been flooded. For Georges Paulin, it suddenly clicked." [2].